Performances of wheat (Triticum aestivum) under various tillage and nitrogen management in sub-Himalayan plains of West Bengal - Mitra, Biplab; Mookherjee, Saikat; Das, Saikat (Journal of Cereal Research, 2014)
A feld experiment was conducted at Instructional Farm, Uttar Banga Krishi Viswavidyalaya, Pundibari, West Bengal during rabi 2008-09 and 2009-10 to asses the performance of wheat under different tillage conditions( conventional tillage, reduced tillage and zero tillage) and nitrogen levels( 100, 125 and 150 kg/ha). It was revealed that zero tillage led to improvement in growth and yield attributing characters, viz., plant height, number of tillers/running meter, number of panicles/ plant, number of flled grains/spike, spike length and test weight. There was a signifcant increase in crop yield (14.29%) of wheat under zero tillage over conventional tillage. Nitrogen uptake in grain and straw were not infuenced signifcantly under various tillage operations, though maximum uptake was recorded with zero tillage due to higher grain yield. Effective tillers per running meter increased by 18.9% with 150 kg/ha of nitrogen over 100 kg/ha. Yield increment was recorded to be 11.86 and 24.40% with application of 125 and 150 kg/ha of nitrogen over 100 kg/ha respectively. Zero tillage exhibited a higher net return (Rs. 20,430.00 /ha) and B-C ratio (2.31) over other tillage practices.